A shape classification scheme for female torso. (January 2023) - Li, Peng; Mitchell, K. Blake
Abstract: This paper presents a shape classification scheme for the female torso, based on anthropometric measurements and 3D body scans from a large scale anthropometric survey. The ability to classify the female body shape is highly desired by the clothing industry and apparel researchers for improving pattern design and fit. In order to objectively classify female torso shapes, we employed principal component analysis on torso related anthropometric measurements and three-dimensional (3D) torso surface data to identify the most dominant measurements. The principal component analysis of the anthropometric measurements show that Waist Circumference is the most dominant variable to define overall female torso size, and that Chest-Waist Drop and Waist-Buttock Drop jointly define the local shape of the torso. Using these findings, a torso shape classification scheme was developed, where nine shape categories were defined from Chest-Waist Drop and Waist-Buttock Drop while torso sizes were divided by Waist Circumference. The distribution of nine shape categories is dependent on the value of Waist Circumference. Mean shape of each shape category was then generated from 3D scans. Highlights: Waist circumference is a dominant measurement for overall torso size. Chest-waist and waist-buttock drops are two critical variables to describe torso shape for female. A novel female torso classification scheme is based on standard deviation of the above three measurements of a population. The distribution of female torso shape classes is dependent on waist circumference.